INTEGRATING LOCAL WISDOM ASSISTED BY INTERACTIVE COMICS IN SOCIAL STUDIES LEARNING: ITS EFFECT ON ELEMENTARY SCHOOL STUDENTS' DIGITAL LITERACY AND CONCEPTUAL UNDERSTANDING - Ni Nyoman Kurnia Wati; Ni Nyoman Lisna Handayani; Komang Trisna Mahartini (Prima Magistra: Jurnal Ilmiah Kependidikan, 2026)
Interactive comics based on local wisdom are seen as capable of providing a solution because they can deliver an enjoyable learning experience while simultaneously strengthening students' cultural identity. This study aims to analyze the effect of integrating local wisdom assisted by interactive comics in Social Studies (IPS) learning on the digital literacy and conceptual understanding of elementary school students. This study used a quantitative approach with a quasi-experimental design in the form of a non-equivalent control group design. The research population consisted of all fifth-grade elementary school students in Cluster III, Buleleng District, in the even semester of the 2025/2026 academic year. The research sample comprised two classes with a total of 68 students, specifically 35 students in the experimental class and 33 students in the control class. The research instruments consisted of a Social Studies conceptual understanding test, a digital literacy questionnaire, learning activity observation sheets, and documentation. Data analysis was conducted quantitatively using descriptive and inferential statistics. Descriptive statistics were used to determine the mean, percentage, standard deviation, and the improvement in students' conceptual understanding and digital literacy. Hypothesis testing was carried out using Manova analysis with the assistance of SPSS. The results of the study showed that: 1) there is a significant difference in digital literacy, with an obtained F-value of 83.339 and a significance of <0.001; 2) there is a significant difference in conceptual understanding, with an obtained F-value of 140.090 and a significance of <0.001; 3) simultaneously, there is a significant difference in both digital literacy and conceptual understanding, with an obtained F-value of 125.293 and a significance of <0.001. Based on the results of the Manova analysis, it can be concluded that learning that integrates local wisdom assisted by interactive comics in Social Studies learning is proven to effectively improve students' digital literacy and conceptual understanding.